Costs of tree seed and seedling supply systems. The cost of integrating genetic diversity into forest landscape restoration. - Neff, D.; Kettle, Christopher J.; Gotor, Elisabetta (Bioversity International, 2019)
Genetic and physiological quality are crucial for the short and long-term success of restoration projects. While physiological quality has a considerable influence on both the germination rate of seedlings and the immediate vitality of the seedling after planting, genetic quality enables a planted population to adapt to a changing environment, and positively correlates with an increased resilience to pests and diseases. Moreover, genetic quality is considered to be an important prerequisite that allows seedlings to establish under prevailing conditions at the planting site and thus to avoid or decrease mortality due to maladaptation. Although there is broad consensus about the advantages of integrating genetic quality into Forest Landscape Restoration (FLR), markets often fail to offer seed of high genetic quality, resulting in genetic quality hardly being considered in current restoration projects. Besides the possible lack of appropriate guidelines or a general lack of awareness about the importance of genetic diversity, a collection strategy that prefers quantity over (genetic) quality might also be a reason for this. It may be economically feasible to collect as many seeds as possible from a few nearby trees, but the disadvantages of this strategy far outweigh the advantages. The resulting lack of genetic quality potentially leads to a (total) failure of a restoration initiatives, which ultimately entails a loss of investment and hence comes with significantly higher costs compared to the costs that were saved during collection. In order to better understand the interrelationships between costs, benefits, properties of the supply chain (e.g., vegetation cover at the planting site), and quality considerations (physical, physiological, plant health, and genetic) we developed a cost model that integrates relevant cost drivers of the tree seed and seedling supply chain into a single cost structure. By presenting a holistic view of relevant cause-effect relationships, we aim to help decision makers and practitioners to take better informed decisions and to create appropriate incentives, which are reflected, for example, in genetic quality-dependent prices for seeds. The model is based on a framework that represents important components of and interrelations within currently applied seed sourcing strategies, as well as associated costs and mechanisms to which these costs are subjected.